Differences in the Effects of Reading and Aerobic Exercise Interventions on Inhibitory Control of College Students With Mobile Phone Addiction - Zhou, Junyi; Wang, Lulu (Frontiers in Psychiatry, 2022)
Although many previous studies have shown that short-time moderate-intensity aerobic exercise can improve one's inhibitory control, some researchers suggested that its effect on inhibitory control is small. Meanwhile, some studies have shown that reading has a positive effect on inhibitory control. Since many studies examining the effect of exercise on inhibitory control used reading as a filler task, it is important to compare their effects. The present study used the antisaccade task as a tool to examine the differences in the effects of aerobic exercise and reading on inhibitory control of college students with mobile phone addiction. 30 healthy college students with mobile phone addiction (range: 17-20 years, mean: 19.2 years) took part in the experiment. Participants were randomly assigned to an aerobic exercise group and a reading group. For the aerobic exercise group, participants were asked to perform moderate-intensity aerobic exercise for 15 minutes. For the reading group, participants were asked to sit quietly and read articles from newspapers for 15 minutes. Each participant's inhibitory control was examined pre- and post-intervention using the antisaccade task. In the antisaccade task, they have to direct their gaze towards the mirror image location of the target appearing parafoveally as quickly and as accurately as possible. The results showed significant main effects of Time (pre-test vs. post-test) on antisaccade latency, variability of antisaccade latency, and error rate. More importantly, a significant interaction of Time (pre-test vs. post-test) and Group (aerobic exercise vs. reading) was found on antisaccade latency. Specifically, the antisaccade latencies in the post-test were significantly shorter than those in the pre-test for the reading group, but the antisaccade latencies in the post-test and pre-test were comparable for the aerobic exercise group. The results of the present study imply that although both exercise and reading have effects on inhibitory control of college students with mobile phone addiction, the effect of reading may be somehow superior to exercise. Moreover, the current results also imply that researchers should be cautious when using reading as a filler task in future studies regarding the effect of aerobic exercise. The limitations of the present study were discussed.